Management of Arabic Intensive Program at High Boarding School of Al Hikmah Batu - Abdul Muhith; Dzun Nur Nafi’ah Muamaroh; Danial Hilmi; Zakiya Arifa (Jurnal Pendidikan Bahasa Arab, 2023)
The maximum efforts in learning arabic students did not show good results. The ?management system which is considered to have not found a bright spot, it is ?considered to need in-depth research to unravel the problem. The purpose of ?this study is to find out: 1) Management of the arabic intensive program at Al ?Hikmah High Boarding School Batu, and 2) Problems in the management. The ?method used in this study was descriptive with qualitative approach. ?Interviews, observations, and documentation became the data collection ?techniques used in this study. The data obtained are then analyzed using ?techniques: data reduction, data presentation, and conclusion/verification. ?From this research, datas were interviews results, observation results, and ?documents of school management, than it can be seen that the management ?program was divided into two: learning program and control program found ?several results stating that the learning program produced good output with ?good program management as well, while the control program produced value ?that is considered lacking due to the existence of an authority mandate system ?and an organizational structure that has not been said to be good. There was no ?decision by the leadership regarding the determination of Arabic zone which ?resulted in the loss of students' awareness in developing and practicing the ?language that had been obtained, as well as the number of Arabic teaching staff ?who were considered insufficient to echo the language which only amounted to ?two teaching staff.